Hubungan Kampanye Politik Calon Presiden 2019 melalui Media Sosial Instagram dengan Keputusan Memilih Mahasiswa Indonesia di Thailand - Laras Weninggalih; M.E Fuady (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The popularity of the use of social media in society, especially young people, makes many politicians choose social media as an effective media for campaigning. In this 2019 Presidential Election, the social media phenomenon Instagram has become the main platform for the Indonesian people to participate in all forms of activities of the two presidential candidates, starting with information about their daily activities, including all content in the form of ideas and views that are promoted by the two pairs of candidates. The content has become the main news intake for Indonesian citizens, especially the segmentation of young people or students. Whether it's Indonesian students at home and abroad. Noted there are around 86,420 Indonesian students spread across 53 countries who will take part in the elections this year. This data was delivered by PPI World Communications Office Deputy Dinda Lisna Amilia in Jawa Pos Online. The purpose of this research is whether there is a relationship between the Political Campaign of Presidential Candidates 2019 through the Official Accounts @jokowi and @prabowo with the Decision to Choose among Indonesian Students in Thailand, then the method used is the correlational method using data collection techniques in the form of questionnaires and questionnaires. The population in this study were Indonesian students in Thailand as users of Instagram social media. The sample in this study amounted to 85 Indonesian students in Thailand out of a total population of 580 people in 2019. The sampling technique used was the Slovin technique. The results of this study are that there is a significant relationship between the political campaigns of the 2019 Presidential Candidates via the official Instagram account @jokowi and @prabowo on the decision to choose among Indonesian students in Thailand with a very high relationship. Abstrak. Kepopuleran penggunaan media sosial di masyarakat terutama kalangan muda, banyak membuat para politisi memilih media sosial sebagai media yang efektif untuk berkampanye. Dalam Pilpres 2019 ini, fenomena sosial media instagram telah menjadi platform utama bagi masyarakat Indonesia dalam mengikuti segala bentuk kegiatan kedua calon presiden dimulai dari informasi mengenai kegiatan kesehariannya, termasuk segala konten berupa gagasan dan pandangan yang dikampanyekan oleh kedua calon pasangan. Konten tersebut telah menjadi asupan berita utama bagi warga negara indonesia khususnya segmentasi kalangan muda atau mahasiswa. Baik itu pelajar Indonesia di dalam negeri maupun di luar negeri. Tercatat terdapat sekitar 86.420 mahasiswa Indonesia yang tersebar di 53 negara yang akan mengikuti pemilu pada tahun ini. Data ini disampaikan oleh Wakil Kantor Komunikasi PPI Dunia Dinda Lisna Amilia dalam Jawa Pos Online. Tujuan dalam penelitian ini adalah apakah terdapat hubungan antara Kampanye Politik Calon Presiden 2019 melalui Akun Resmi Instagram @jokowi dan @prabowo dengan Keputusan Memilih di Kalangan Mahasiswa Indonesia di Thailand, lalu metode yang digunakan adalah metode korelasional dengan menggunakan teknik pengumpulan data berupa kuisioner dan angket. Populasi dalam penelitian ini adalah Mahasiswa Indonesia di Thailand sebagai pengguna media sosial instagram. Sampel dalam penelitian ini berjumlah 85 Mahasiswa Indonesia di Thailand dari total jumlah populasi 580 orang pada tahun 2019. Teknik penarikan sampel yang digunakan adalah menggunakan teknik Slovin. Hasil dari penelitian ini adalah terdapat hubungan yang signifikan antara kampanye politik Calon Presiden 2019 melalui akun resmi Instagram @jokowi dan @prabowo terhadap keputusan memilih di kalangan mahasiswa Indonesia di Thailand dengan hubungan yang sangat tinggi.